2013
DOI: 10.1051/e3sconf/20130141010
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impacts of gold mining assessing the impacts of gold mining operations on river sediments and water samples from ilesa west local government area ILESA West Local Government Area of Osun State, Nigeria

Abstract: Abstract. Gold 1 N. A total of 51 stream water and sediment samples were randomly collected from water sources available to the communities. Stream water samples collected were analyzed for heavy metals using atomic absorption spectrophotometer (AAS) while associated stream sediments were analyzed with x-ray fluorescence spectrometer (XRF). Heavy metals analyzed in both sample types include As, Cu, Cd, Pb, Fe, Cr, Mn, Zn, Zr, and Sr. Results obtained showed the stream waters to be richly concentrated with to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Field observations further revealed that some of the local farmers and residents, yield their lands to the miners in exchange for monetary compensation. This could explain the reason for large number of pits discovered in the study area (Makinde et al, 2014;Adeoye 2015). 25% of those surveyed concurred that mining operations in their neighborhoods truly destroyed their forest and land.…”
Section: The Effects Of Mining Activities On the Local Communitiesmentioning
confidence: 89%
“…Field observations further revealed that some of the local farmers and residents, yield their lands to the miners in exchange for monetary compensation. This could explain the reason for large number of pits discovered in the study area (Makinde et al, 2014;Adeoye 2015). 25% of those surveyed concurred that mining operations in their neighborhoods truly destroyed their forest and land.…”
Section: The Effects Of Mining Activities On the Local Communitiesmentioning
confidence: 89%
“…4 The potential adverse impacts of mining have also been asserted to include displacement of local people from ancestral lands, marginalization, and oppression of people belonging to lower economic classes. 5 Cyanide is one of the few poisons chemicals that it antidotes exist if inhaled or injected by any organisms which can cause a dramatic and severe poisoning that can quickly result in death. It produces histotoxic (intracellular) hypoxic poisoning by the binding of the Citation: Okunola OV, Komolafe OO, Okonji RE, et al Environmental risk assessments of uses cyanide in gold extraction on water quality parameters and its effect on rhodanese activities in selected organs of coptodon zillii in igun reservoir, Southwestern, Nigeria.…”
Section: Introductionmentioning
confidence: 99%